On pseudoanalyticity of continuous functions with constant $σ$-extension - Bondar, A. V.; Lukyanova, E. A. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
The theorem on pseudoanalyticity of continuous functions with constant $σ$-extension is proved; this is an analog of the well known results due to Bohr, Rademacher, Men'shov, and Trokhimchuk concerning the analyticity of functions with constant extension.